Surgical approach incisions in the abdomen of the newborn, infant and child - Cabrera Roca, María Teresa (Cirugía del Uruguay, 2020)
a) Transversal inc1s10ns for oclusive problems of the newly born are advised. b) Slating incisions can only be performed when you have a right diagnosis, because its range is limited. ) If we are forced to perform vertical incitions, the skin incision must not coincide with that of the deeper layers, being these in "Y" or in "Z". d) According to our criteria these principles are absolute for newly born and lactants of less than one year, and they are advisable in first infancy. e) We advise to take into consideration these principles and apply them in metabolic disturbances, catabolizing diseases, cortisone medication or possibility of bowel ileum in se·cond infancy, according to the surgical possibilities of _these ages. We don't object the performance of paramedial incisions to normal grown-up children spécially when the have traumatic disturbances.